KOMITMEN GURU DALAM MENINGKATKAN KOMPETENSI PROFESIONAL SEBAGAI PENDIDIK - Serlinda Serlinda; Zakaria Zakaria (Manajer Pendididikan, 2019)
Abstract: this research aims to describe the teacher commitment in improving professional competence as educator in Senior High Schol 1 Muara Pinang. The special purpose of this research is ti know how is the teacher commitment un improving education qualifications, teaching and learning innovation in scientific activities, teaching, commitment in eacher organitation as well as anything that affects the teacher’s commitment to improving professional competation as education. The method of this research is descriptive qualitative method. The subject of this research is teacher. The tecnic of collecting the data is used interview. Observation, documentation. The above research can be conclude that the teacher commitment in improving professional competence as educator by following magister program, training, implementating the learning process well, following seminar, worshop and which may effect the teacher commitment in improving professional competence is the facilities and infrastructure alsa motivation of the teacher in self.Keyword : Teacher, Comitment, Competence Professional